2019
DOI: 10.25103/jestr.126.26
|View full text |Cite
|
Sign up to set email alerts
|

Modified Environmental Adaptation Method and its Application in Test Case Generation

Abstract: A modified environmental adaptation method (MEAM) is the modified version of environmental adaptation method. The MEAM algorithm is operates based on adaptation and alteration operator to find the solution from the huge search space. The alteration operator in MEAM to evade the incidence of being struck into local minima. To test the performance of on real world application MEAM is applied in test case generation problem and proved to better than PSO -TVAC algorithm. From the results it has been observed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Montero et al [7] discussed a VRP with pickup and delivery (VRPPD) and developed a local search program based on integer linear programming (ILP), and the results of the calculation example verified the potential of the method in solving VRPPD. Tiwari et al [8] proved a modified environmental adaptation method can evade the incidence of being struck into local minima. Alaia et al [9] investigated a multi-vehicle, multidepot pickup and delivery problem with time windows and solved a benchmark example using a GA and PSO algorithm, and the results showed that the GA algorithm is better than the PSO algorithm.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Montero et al [7] discussed a VRP with pickup and delivery (VRPPD) and developed a local search program based on integer linear programming (ILP), and the results of the calculation example verified the potential of the method in solving VRPPD. Tiwari et al [8] proved a modified environmental adaptation method can evade the incidence of being struck into local minima. Alaia et al [9] investigated a multi-vehicle, multidepot pickup and delivery problem with time windows and solved a benchmark example using a GA and PSO algorithm, and the results showed that the GA algorithm is better than the PSO algorithm.…”
Section: State Of the Artmentioning
confidence: 99%
“…As the pickup point and delivery point presented a one-to-one corresponding relation in this study, first, the pickup points were randomly permutated and combined to form a chromosome during the coding process, the vehicles were inserted into multiple positions of the chromosome, and the delivery points were randomly inserted at each pickup point served by each vehicle. Taking five cargo owners and two vehicles as an example, first, a chromosome (2, 3, 5, 4, 1) was randomly generated, the vehicles were inserted into the chromosome to obtain (11,2,3,5,12,4,1), and the delivery points were inserted to acquire (11,2,3,7,8,5,10,12,4,9,1,6). Finally, the formed chromosome showed that the first vehicle provided the delivery service for cargo owners 2, 3, and 5, and the second vehicle provided the delivery service for cargo owners 1 and 4.…”
Section: Algorithm Design (1) Simulation Of Cargo Transport O2o Platform Distribution Design Via Anylogicmentioning
confidence: 99%